Towards a framework for patient-centred care coordination: a scoping review protocol. Issue 12 (1st December 2022) - Khanna, Aishwarya; Fix, Gemmae M; Anderson, Ekaterina; Bolton, Rendelle E; Bokhour, Barbara G; Foster, Marva; Smith, Jason G; Vimalananda, Varsha G
Abstract : Introduction: Patient-centred care and care coordination are each key priority areas for delivering high quality healthcare. However, the intersection between these two concepts is poorly characterised. We theorise that greater advancements in healthcare quality could be realised when care is organised in a way that aligns with patients' preferences, needs and values across every level of the healthcare system. There is currently no published review that describes the intersection of patient-centred care and care coordination. We will undertake a scoping review that will be foundational to the development of a conceptual framework for patient-centred care coordination that integrates and synthesises the overlap between these two concepts and describe how it manifests across levels of the healthcare system. Methods and analysis: A multidisciplinary team of reviewers will conduct a scoping review of published and grey literature to identify and synthesise key concepts at the intersection of patient-centred care and care coordination, following Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews guidance for scoping reviews. Databases we will use in our search include PubMed, CINAHL, Embase, Social Sciences Abstracts, Nursing and Allied Health Premium, Health and Medical Collection, and PsycINFO. Articles will be included that are English-language; published during or after 2001; describe a theory, conceptual model, theoretical framework or definition that addresses both patient-centred care and care coordination. Articles will be excluded if they do not address the intersection of patient-centred care and care coordination; discuss a patient-centred medical home without discussion on patient-centred care concepts; or discuss a paediatric, inpatient or palliative care setting. A data extraction template will facilitate qualitative thematic analysis and findings will be synthesised into a conceptual framework. Ethics and dissemination: This work does not require ethics approval. A preliminary framework will be presented to a group of patient stakeholders for refinement before dissemination through a peer-reviewed journal and conference presentations.